Effect of NLRP3 inflammasome induced astrocyte phenotype alteration in morphine tolerance - Yuan, Zhenyu; Lu, Boxuan; Zhang, Meiling; Lu, Yinxiao; Wang, Zhihui; Zhang, Wenhao; Cheng, Hao; Wu, Zhifang; Ji, Qing (Frontiers in Pharmacology, 2024)
Introduction Morphine is a widely used analgesic, but its prolonged use often leads to tolerance, limiting its therapeutic efficacy. Research implicates the NLRP3 inflammasome and reactive astrocytes in the development of morphine tolerance, with reactive astrocytes classified into A1 neurotoxic and A2 neuroprotective phenotypes. This study explores the role of the NLRP3 inflammasome and the transformation of astrocyte phenotypes in the progression of morphine tolerance. Methods A model of morphine tolerance was established by administering morphine intrathecally for seven consecutive days. To inhibit NLRP3 inflammasome activation, we coadministered MCC950, a selective NLRP3 inhibitor. Thermal withdrawal latency was used to assess tolerance development. Protein and mRNA levels of GFAP, IL-18, NLRP3, C3 (A1 marker), and S100A10 (A2 marker) in the spinal cord were measured using Western blotting (WB) and real-time quantitative polymerase chain reaction (RT-qPCR). Immunofluorescence was employed to assess the colocalization of C3 and GFAP. Results Seven days of morphine administration induced tolerance, which was associated with increased levels of GFAP, IL-18, NLRP3, and C3, and a decreased level of S100A10. Coadministration of morphine and MCC950 significantly slowed the development of morphine tolerance and reversed changes in NLRP3, IL-18, GFAP, C3, and S100A10 protein levels. Discussion Our findings indicate a significant link between NLRP3 inflammasome activation and morphine tolerance, suggesting that NLRP3 contributes to the transformation of astrocytes to the A1 phenotype. Inhibiting NLRP3 inflammasome activation holds promise in reversing astrocyte phenotype changes, potentially mitigating morphine tolerance.